2017
DOI: 10.1108/jap-05-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Researching the financial abuse of individuals lacking mental capacity

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…This study has demonstrated that a suspicion of financial abuse perpetrated towards older people is not uncommon among bank managers' experiences; all participants had multiple examples of case suspicions. Similar to the literature on financial abuse of older people (Gilhooly et al, 2013;Harries et al, 2014;Dalley et al, 2017), the case accounts reflected many types of financial abuse, both related to family members and opportunism (rogue traders, lottery scams). A systematic review and meta-analysis (Burnes et al, 2017) identified that a minimum of one in 18 older people living the community are subject to scams every year.…”
Section: Cases Involving Issues Related To Capacitymentioning
confidence: 81%
See 1 more Smart Citation
“…This study has demonstrated that a suspicion of financial abuse perpetrated towards older people is not uncommon among bank managers' experiences; all participants had multiple examples of case suspicions. Similar to the literature on financial abuse of older people (Gilhooly et al, 2013;Harries et al, 2014;Dalley et al, 2017), the case accounts reflected many types of financial abuse, both related to family members and opportunism (rogue traders, lottery scams). A systematic review and meta-analysis (Burnes et al, 2017) identified that a minimum of one in 18 older people living the community are subject to scams every year.…”
Section: Cases Involving Issues Related To Capacitymentioning
confidence: 81%
“…In Ireland, while there is evidence of financial abuse of older people through HSE safeguarding reports (National Safeguarding Office, 2017, 2018, 2019) and comments in a recent Issues Paper (Law Reform Commission, 2019), its scope and volume has not been quantified and, similar to other countries, a true estimate is elusive (Phelan et al , 2014; Wood and Lichtenberg, 2017; Deane, 2018). Modes of financial abuse perpetration are multiple (Conrad et al , 2011; Dalley et al , 2017) and may occur without the knowledge of the older person, yet have devastating impacts such as loss of confidence to live independently, distress, or mental health problems such as anxiety and depression (Davidson et al , 2015). Similarly, the loss of fiscal resources can constitute a threat to the economic security of the older person (Greene, in press), while any return to financial stability may be limited as older people do not have the same capacity to re-enter the workforce (Hafemeister, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of impact experienced by victims, the modus operandi , financial loss, emotional and social impact of fraud show wide variation with some victims significantly impacted (Cross et al , 2016; Whitty and Buchanan, 2015) and others for whom the impact appears to be less (Blakeborough and Correia, 2018). And finally, some fraudsters are known to single out and target specific individuals on multiple occasions: individuals within the elderly community or those with a mental impairment have been highlighted (Dalley et al , 2017; NAO, 2016; Phillips, 2017). Repeat offending against individuals can also be achieved by means of social engineering or grooming (Age UK, 2015; Whitty, 2018) and is inherent in recognised fraud categories such as recovery fraud[2] (Home Office, 2018b).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…119 In a study on the financial abuse of adults lacking capacity, Daley et al looked at a sample of 34 cases heard in the Court of Protection between 1 January and 9 November 2015, to study the characteristics of financial abuse by both attorneys and deputies. 120 In eighteen of these 34 cases, the court was confronted with a situation in which the attorney allegedly had breached his authority or had failed to act in the bests interests of the adult concerned. 121 Examples of situations raising suspicions or indicating misbehaviour by the attorney included: co-mingling of the adult's and attorney's assets; a failure to pay the adult's care home fees; donations exceeding the permissible amount and chaotic management of the adult's assets.…”
Section: Law In Actionmentioning
confidence: 99%